GENDER SEBAGAI SUMBER POLITIK DALAM KEWARGANEGARAAN SOSIAL (PERAN PEREMPUAN DI PARLEMEN INDONESIA) - Mariana Mariana; Aip Piansah; Uu Nurul Huda; Ahmad Rifai (Pusat Studi Gender dan Anak (PSGA), Universitas Islam Negeri Syarif Hidayatullah, 2022)
Abstract. Women's political presence in the public sphere, including their political participation and representation, is an important, though not equal element for Indonesian citizens in their capacity as participatory and sufficient in multiple strategies to create gender equality. This paper aims to find out about gender as a political source in social citizenship, especially the role of women in the Indonesian parliament. Researchers use normative legal research methods (Normative Legal Research), a type of qualitative research The legal materials used in this study include primary, secondary, and tertiary legal materials. The collection of secondary legal materials is carried out by literature studies. The existence of women in parliament gives a new spirit in the gender equality order as policy makers on governance issues. In its existence, affirmative action is still a problem for women in improving the quality of their representation in parliament. Abstrak. Kehadiran politik perempuan di ranah publik, termasuk partisipasi dan keterwakilan politik mereka, merupakan elemen penting, meskipun tidak sama bagi warga Negara Indonesia dalam kapasitasnya sebagai partisipatif dan cukup dalam strategi berganda untuk menciptakan kesetaraan gender. Tulisan ini bertujuan untuk mengetahui terkait gender sebagai sumber politik Dalam kewarganegaraan sosial khususnya peran perempuan di parlemen Indonesia. Peneliti menggunakan metode penelitian hukum normatif (Normative Legal Research),jenis penelitian kualitatif. Bahan hukum yang digunakan dalam penelitian ini di antaranya adalah bahan hukum primer, sekunder, dan tersier. Pengumpulan terhadap bahan hukum sekunder dilakukan dengan studi kepustakaan. Keberadaan perempuan dalam parlemen memberikan semangat baru dalam tatanan kesetaraan gender sebagai pengambil kebijakan terhadap isu-isu pemerintahan. Dalam keberadaannya tindakan afirmasi masih menjadi persoalan bagi perempuan dalam meningkatkan kualitas keterwakilannya di parlemen. TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack// This page is in English Translate to Indonesian AfrikaansAlbanianAmharicArabicArmenianAzerbaijaniBengaliBulgarianCatalanCroatianCzechDanishDutchEnglishEstonianFinnishFrenchGermanGreekGujaratiHaitian CreoleHebrewHindiHungarianIcelandicIndonesianItalianJapaneseKannadaKazakhKhmerKoreanKurdish (Kurmanji)LaoLatvianLithuanianMalagasyMalayMalayalamMalteseMaoriMarathiMyanmar (Burmese)NepaliNorwegianPashtoPersianPolishPortuguesePunjabiRomanianRussianSamoanSimplified ChineseSlovakSlovenianSpanishSwedishTamilTeluguThaiTraditional ChineseTurkishUkrainianUrduVietnameseWelsh Always translate English to IndonesianPRO Never translate English Never translate journal.uinjkt.ac.id